Love me, love me not. 7 - Sakisaka, Io; Thistlethwaite, Nancy (Shojo beat manga., 2021)
"Love and friendship have become quite complicated for these four friends. Akari seeks comfort from Kazuomi after an ex-boyfriend has some harsh words for her. Yuna is about to hear a love confession, but is it from the boy she likes?"--Provided by publisher.